Condition-Specific Oral Health-Related Quality of Life (CS-OHRQoL) measures in Orthodontics- A Narrative Review - Peter, Elbe; J, Monisha (Orthodontic Journal of Nepal, 2022)
Outcomes pertaining to orthodontics can be either ‘disease’ outcome or ‘treatment’ outcome. The scales used for outcome assessment are usually the same for both and can be classified as generic or condition-specific. Generic scales are used in general for a variety of clinical conditions in dentistry, whereas condition-specific scales are used for specific problems like malocclusion. Due to the peculiar nature of orthodontic problems that do not fall into the definition of a disease, generic scales are of little use and condition-specific ones are recommended. The present article aims to provide a summary of the available condition-specific patient-reported outcome measures in orthodontics and perform a critical analysis of the same.